2021
DOI: 10.21037/atm-21-5066
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of chidamide and venetoclax on apoptosis in acute myeloid leukemia cells and its mechanism

Abstract: Background: Acute myeloid leukemia (AML) is a hematological malignancy with a low remission rate and high recurrence rate. Overexpression of the antiapoptotic protein Bcl-2 is associated with a lower overall survival rate in AML patients. Venetoclax (ABT199) is a selective inhibitor of Bcl-2 that has a significant effect in AML, but single-drug resistance often occurs due to the high expression of Mcl-1 protein. Studies have confirmed that chidamide can downregulate the expression levels of Bcl-2 and Mcl-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Furthermore, similar strategies involving SAHA and decitabine have been tested in clinical trials and have shown promising effects in patients with relapsed ALL ( 18 , 19 , 65 ). Low doses of decitabine and SAHA caused cell death in leukemic cells and reduced p21 levels without significant changes in normal peripheral blood lymphocytes ( 66 ). Additionally, pretreatment with SAHA and decitabine can enhance the cytotoxicity of chemotherapy in relapsed childhood B-ALL, suggesting that epigenetic mechanisms play a role in the acquisition of chemoresistance during ALL recurrence ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, similar strategies involving SAHA and decitabine have been tested in clinical trials and have shown promising effects in patients with relapsed ALL ( 18 , 19 , 65 ). Low doses of decitabine and SAHA caused cell death in leukemic cells and reduced p21 levels without significant changes in normal peripheral blood lymphocytes ( 66 ). Additionally, pretreatment with SAHA and decitabine can enhance the cytotoxicity of chemotherapy in relapsed childhood B-ALL, suggesting that epigenetic mechanisms play a role in the acquisition of chemoresistance during ALL recurrence ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some types of leukemia and lymphoma, cancer cells evade the natural mechanism of apoptosis by overexpressing Bcl-2, leading to the oversurvival of cancer cells [ 23 ]. During Venetoclax treatment, acquired drug resistance is a common phenomenon, and the compensatory high expression of Mcl-1 may be one of the causes of drug resistance in AML cells [ 24 ]. According to previous reports, both class I HDAC inhibitors and Venetoclax could induce apoptosis and perform a synergistic effect [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…During Venetoclax treatment, acquired drug resistance is a common phenomenon, and the compensatory high expression of Mcl-1 may be one of the causes of drug resistance in AML cells [ 24 ]. According to previous reports, both class I HDAC inhibitors and Venetoclax could induce apoptosis and perform a synergistic effect [ 24 ]. As the IC 50 of 25c measured in the above experiments was 340.1 ± 82.5 nM in the MV4-11 cell line, showing the more obvious effect among the four cell lines, we selected the MV4-11 cell line for the combination cell assay and analyzed the data according to the Chou–Talalay method [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies ( 14 16 ) have shown promising results with the combination therapy of venetoclax and other targeted drugs. For example, the combination of venetoclax, azacitidine, and daunorubicin achieved a higher complete remission rate in newly diagnosed acute monocytic leukemia patients.…”
Section: Discussionmentioning
confidence: 99%